Innovation Implementation in Supply Chain Management: Research Based On Organic Farming Operation - Wan Nur Zawahir, Wan Abd Wahab; Shariman, Mustafa (2009)
Agriculture is one of the key sectors for international trade that supply foods to the world population. It is progressively becoming a profitable business venture. Malaysia has a large potential to develop its organic market as the local organic farming activities is increasing rapidly. Even though the growth is a bit slow, it is noted that most people who purchased organic foods are very committed to the product. However due to some uncertainty among the organic supply chain system, there is a need for common reference and practice implemented among organic actors. Regarding to this matter, this study will explore on organic supply chain to encourage the future incremental growth of organic market and identify the root causes to the problems occurring. This study will also focus on innovation aspects along the supply chain management system. There is an urgent need for innovation in shifting organic sector paradigm to be more suitable to the current organic market consumer requirements. The research is aimed to highlight the innovation that should be implemented in the supply chain system of organic agriculture sector as well as suggesting future innovation initiative to the overall organic operation.